Review of fracture cases in cats and dogs presented to the Veterinary Teaching Hospital UPM - Mohamed Yusof, Loqman; Abu Bakar @ Zakaria, Md Zuki; Y., Ani; Mohd Yusof, Ainul Yuzairi; Ibrahim, Rashid (Universiti Putra Malaysia Press, 2004)
A review of the distribution of fracture cases in cats and dogs presented in the UVH-UPM within period of 10 years (1991 to 2001) are discussed.